Factors influencing intention to use online food delivery service between local and foreign university students in Malaysia - Lai, Hui Yee (2019)
Nowadays, online food delivery (OFD) service is going viral in Malaysia. Since it brings numerous advantages for the consumers, it has been attracting many people to use it in their daily life. Instead of going to the physical restaurant to purchase food, the consumers are able to purchase food through online platform and use the delivery service. This research is to examine the independent variables which are including time saving, cost saving, perceived usefulness and prior online purchase experience towards the dependent variable of intention to use OFD service. The target respondents will be the local and foreign university students who are studying in Malaysia. Besides that, there are 300 sets of questionnaires have been distributed via Google Form to respondents by using convenient sampling method. After that, the data collected will be analysed by using Statistical Package for Social Science (SPSS). Also, there will be Reliability Test and Multiple Regression Analysis that have been conducted. In this research project, the results show that all of the independent variables have positive or significant relationship towards the intention to use OFD service. Moreover, this research provides a clear data and information about the factors that may influence intention to implement OFD service in daily life. Lastly, there will be limitations towards this research project and recommendations will be provided for further research in the future.